Assessment of Teachers' Exposure to Noise in Selected Primary Schools - AUGUSTYŃSKA, Danuta; KACZMARSKA, Anna; MIKULSKI, Witold; RADOSZ, Jan (Archives of Acoustics, 2013)
The assessment of teachers' exposure to noise in primary schools was carried out on the basis of: questionnaire studies (covering 187 teachers in 3 schools), noise measurements at the teachers' workplaces, measurements of the school rooms acoustic properties (reverberation time and speech transmission index STI in 72 classrooms), analysis of statistical data regarding hazards and occupational diseases in the education sector. The studies have shown that noise is the main factor of annoyance in the school environment. Over 50% of questioned teachers consider noise as annoying and near 40% as very annoying or unbearable. A-weighted equivalent continuous sound pressure levels measured in classrooms, teacher rooms and common rooms are in the range of 58-80 dB and they exceed 55 dB (criteria of noise annoyance). The most frequently reported subjective feelings and complaints (over 90%) are: growth of psychical and emotional tension, irritation, difficulties in concentrating, hoarseness, cough. Noise in schools is also a harmful factor. High A-weighted equivalent continuous sound pressure levels ranging from 80 to 85 dB, measured in corridors during pauses and in sports halls, can cause the risk of hearing damage among PE teachers and persons oversensitive to noise. The latter concerns both teachers and pupils. High background noise levels (55-65 dB) force teachers to raise their voice. It can lead to the development of an occupational disease - chronic voice disorders due to excessive vocal effort lasting for at least 15 years. In the education sector 785 new cases of this disease were reported only in 2008. Poor acoustics in classrooms (reverberation time ranging from 0.8 to 1.7 s, STI